Validation of PAS Kinase, a Regulator of Hepatic Fatty Acid and Triglyceride Synthesis, as a Therapeutic Target for Nonalcoholic Steatohepatitis. Issue 5 (24th March 2020) - Swiatek, Wojciech; Parnell, K. Mark; Nickols, G. Allen; Scharschmidt, Bruce F.; Rutter, Jared
Abstract : Hyperactivation of sterol regulatory element binding protein 1c (SREBP‐1c), which transcriptionally induces expression of enzymes responsible for de novo lipogenesis and triglyceride (TG) formation, is implicated in nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH) pathogenesis. Posttranslational SREBP‐1c maturation and activation is stimulated by the protein per–arnt–sim kinase (PASK). PASK‐ knockout mice are phenotypically normal on a conventional diet but exhibit decreased hypertriglyceridemia, insulin resistance, and hepatic steatosis on a high‐fat diet. We investigated the effects of pharmacologic PASK inhibition using BioE‐1115, a selective and potent oral PASK inhibitor, in Zucker fatty ( fa ) /fa) rats, a genetic model of obesity, dyslipidemia, and insulin resistance, and in a dietary murine model of NAFLD/NASH. Female Zucker ( fa/fa ) rats and lean littermate ( fa /+) controls received BioE‐1115 (3‐100 mg/kg/day) and/or omega‐3 fatty acids, and blood glucose, hemoglobin A1c, glucose tolerance, insulin, and serum TG were measured. C57BL/6J mice fed a high‐fat/high‐fructose diet (HF‐HFrD) were treated with BioE‐1115 (100 mg/kg/day) or vehicle. Body weight and fasting glucose were measured regularly; serum TG, body and organ weights, and liver TG and histology were assessed at sacrifice. Messenger RNA (mRNA) abundance of SREBP‐1c target genes was measured in both models. In Zucker rats, BioE‐1115 treatment produced significant dose‐dependent reductions in blood glucose, insulin, and TG (all greater than omega‐3 fatty acids) and dose dependently restored insulin sensitivity assessed by glucose tolerance testing. In HF‐HFrD mice, BioE‐1115 reduced body weight, liver weight, fasting blood glucose, serum TGs, hepatic TG, hepatic fibrosis, hepatocyte vacuolization, and bile duct hyperplasia. BioE‐1115 reduced SREBP‐1c target mRNA transcripts in both models. Conclusion: PASK inhibition mitigates many adverse metabolic consequences associated with an HF‐HFrD and reduces hepatic fat content and fibrosis. This suggests that inhibition of PASK is an attractive therapeutic strategy for NAFLD/NASH treatment. Abstract : PAS kinase (PASK), a broadly evolutionarily conserved kinase, is nutrient‐responsive metabolic regulator that is required for the proteolytic maturation of sterol regulatory element‐binding protein (SREBP)‐1c, a transcriptional activator of genes that encode the enzymes that catalyze fatty acid and triglyceride production. We have demonstrated in two complementary animal models, a genetic model of obesity, dyslipidemia and insulin resistance (Zucker (fa/fa) rats) and a dietary murine model of NAFLD/NASH, that pharmacological inhibition of PASK mitigates many of adverse metabolic consequences associated with NASH, including hypertriglyceridemia and insulin resistance, and significantly reduces liver fat and fibrosis. Our findings collectively suggest that inhibition of PASK is an attractive therapeutic strategy for NAFLD/NASH treatment.